Particle Beam Radiation Therapy for Adenoid Cystic Carcinoma of the Nasal Cavity and Paranasal Sinuses - Hu, Weixu; Hu, Jiyi; Huang, Qingting; Gao, Jing; Yang, Jing; Qiu, Xianxin; Kong, Lin; Lu, Jiade J. (Frontiers in Oncology, 2020)
Background: Sinonasal adenoid cystic carcinoma (SNACC) presents a challenge to oncologists due to its complex anatomy and poor prognosis. Although radiation therapy, either definitive or adjuvant to surgery, is an important part of the multidisciplinary management of SNACC, photon-based radiotherapy yielded suboptimal local control. The purpose of this study was to report the clinical results of a large patient cohort treated with particle beam radiation therapy. Methods: Patients with SNACC that received proton beam therapy (PBT), carbon-ion radiotherapy (CIRT) or a combination of CIRT and PBT between May 2015 and May 2019 were included in the analysis. Three patients were treated with PBT, 17 with CIRT and 18 received PBT and a CIRT boost. Overall survival (OS), progression-free survival (PFS), local control (LC), regional control (RC) and distant metastasis-free (DMF) rates were calculated using the Kaplan-Meier method. Toxicities were reported using the CTCAE (version 4.03). Results: A total of 38 patients were included in this analysis. Of these patients, 12 had recurrent disease, including 10 whose previous photon-based RT had failed. The most common primary tumor site was the maxillary sinus. Thirty-six patients (94.7%) suffered from locally advanced disease (T3-4). After a median follow-up of 27.2 months, the 3-year OS, PFS, LC, RC, and DMF rates were 96.7%, 80.6%, 90.0%, 100%, and 88.7%, respectively. No acute toxicities of grade 3 or above were observed. Two patients experienced grade 3 xerostomia or vision decreased, and one patient died of hemorrhage. Conclusion: PBT, CIRT or a combination of CIRT and PBT appeared to be a promising treatment option for SNACC and produced satisfactory local control and toxicity profile. Longer follow-up is needed to verify the long-term benefit of particle-beam radiation therapy (PBRT) for patients with SNACC.